On the multiwavelength emission from gamma ray burst afterglows - Petropoulou, M.; Mastichiadis, A. (2009)
Aims: Drawing an analogy with active galactic nuclei, we investigate the one-zone synchrotron self-compton (SSC) model of gamma ray bursts (GRB) afterglows in the presence of electron injection and cooling both by synchrotron and SSC losses. Methods: We solve the spatially averaged kinetic equations which describe the simultaneous evolution of particles and photons, obtaining the multi-wavelength spectrum as a function of time. We back up our numerical calculations with analytical solutions of the equations using various profiles of the magnetic field evolution under certain simplifying assumptions. Results: We apply the model to the afterglow evolution of GRBs in a uniform density environment and examine the impact various parameters have on the multiwavelength spectra. We find that in cases where the electron injection and/or the ambient density is high, the losses are dominated by SSC and the solutions depart significantly from the ones derived in the synchrotron standard cases.
Keywords: acceleration of particles; Astrophysics - High Energy Astrophysical Phenomena; Gamma Rays: Bursts; radiation mechanisms: non-thermal